2008
DOI: 10.1592/phco.28.9.1125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dosing Recommendations for Antimicrobial Drugs Based on Two Methods for Assessing Kidney Function: Cockcroft‐Gault and Modification of Diet in Renal Disease

Abstract: Discordance rates for drug dosing ranged from 22.8-36.3% between the MDRD and Cockcroft-Gault methods for estimating GFR. Although use of the MDRD equation is a well-accepted and accurate method of estimating GFR to stage chronic kidney disease, our results demonstrated a significant difference in drug dosing regimens between the MDRD method and the Cockcroft-Gault method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 21 publications
10
55
1
3
Order By: Relevance
“…22 Although these equations have limitations, both the CG and MDRD equations have been shown to correlate relatively well with measured glomerular filtration rate (GFR), 22 but differences in medication dose recommendations have been reported depending on which equation is used. [23][24][25] An analysis of the Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes With Early Implementation of the ACC/AHA Guidelines (CRUSADE) registry was conducted to compare the CG and MDRD equations with regard to the recommended doses of eptifibatide, tirofiban, and enoxaparin. 23 Results of this analysis showed a 20% difference in CKD classification between the 2 equations.…”
Section: Methods Of Estimating Renal Function For Drug Dosingmentioning
confidence: 99%
“…22 Although these equations have limitations, both the CG and MDRD equations have been shown to correlate relatively well with measured glomerular filtration rate (GFR), 22 but differences in medication dose recommendations have been reported depending on which equation is used. [23][24][25] An analysis of the Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes With Early Implementation of the ACC/AHA Guidelines (CRUSADE) registry was conducted to compare the CG and MDRD equations with regard to the recommended doses of eptifibatide, tirofiban, and enoxaparin. 23 Results of this analysis showed a 20% difference in CKD classification between the 2 equations.…”
Section: Methods Of Estimating Renal Function For Drug Dosingmentioning
confidence: 99%
“…Toutes ces é tudes sont cependant des simulations et nous en ré sumons les principales dans le Tableau 2 [49,50,52,[54][55][56][57][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. À la vue de ce tableau, le moins que l'on puisse dire est que les é tudes ne sont pas toujours d'une qualité mé thodologique irré prochable (notamment en termes de « cré atinine »), que les mé thodologies et les simulations sont parfois assez diffé rentes, et enfin que les ré sultats de ces publications, en termes du choix de la formule, sont trè s contradictoires.…”
Section: Le Choix De La Formule : Que Nous Dit La Litte´rature ?unclassified
“…Recommendations about drug dosing in CKD and the related pharmacokinetic studies have, in many cases, preceded use of newer eGFR equations. Several studies have demonstrated a substantial discordance between drug dosing recommendations established via stateof-the-art estimates of kidney function and those based on older estimating equations, such as Cockcroft-Gault (20)(21)(22). The full implications of this discordance on safety of patients with CKD have yet to be determined.…”
Section: Accounting For Standardized Kidney Function Measurement and mentioning
confidence: 99%